1962
DOI: 10.1126/science.138.3540.594
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Developing Mammalian Egg: Removal of the Zona Pellucida

Abstract: The zona pellucida may be removed from all stages of the mouse egg by digestion with pronase. Cumulus and corona cells are also dispersed by the enzyme. No change in membrane disgestibility occurs at fertilization. In tests thus far of two-cell eggs and later stages, development continues. Blastocysts exhibit "hatching" behavior despite absence of the zona. Functions of the zona include maintenance of the normal cleavage pattern and prevention of egg fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
87
0
2

Year Published

1965
1965
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(90 citation statements)
references
References 8 publications
1
87
0
2
Order By: Relevance
“…Embryos were flushed from oviducts and tubo-uterine junctions around noon on the third day after mating (vaginal plug, day 1). Zonae pellucidae were removed from eight-cell embryos by treatment with 0.5% pronase in PBS for 3-5 min (Mintz 1962). After rinsing the embryos in three changes of M2 medium, they were transferred to Dulbecco's salt solution, which was devoid of Ca and Mg ions, for 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…Embryos were flushed from oviducts and tubo-uterine junctions around noon on the third day after mating (vaginal plug, day 1). Zonae pellucidae were removed from eight-cell embryos by treatment with 0.5% pronase in PBS for 3-5 min (Mintz 1962). After rinsing the embryos in three changes of M2 medium, they were transferred to Dulbecco's salt solution, which was devoid of Ca and Mg ions, for 15 min.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that early implantation stage embryos from which the zona pellucida was removed developed into blastocysts by in vitro culture without feeders (Mintz, 1962). In the present study, zona-free embryos that were cultured on feeders differed developmentally from intact embryos.…”
Section: Discussionmentioning
confidence: 53%
“…However, Ohno and coworkers found that both X chromosomes were euchromatic (indicating functional capacity) in oogonia and oocytes from fetal ovaries of the rat, hamster, human and mouse (Ohno, Kaplan and Kinosita, 1961 ; Ohno and !/Veiler,1961 ;Ohno, Klinger and Atkin, 1962 ;Ohno, 1963). Recent biochemical observations have confirmed that both Xs are functional in oocytes (Epstein, 1969 ;Gartler et al, 1972 ;Gartler, Liskay and Gant, 1973 ;Kozak, McLean and Eicher, 1974 ;Gartler, Andina and Gant, 1975 ; Mangia, Abbo-Halbach and Epstein, 1975) and probably also in oogonia (Migeon and Jelalian, 1977 (Tarkowski, 1961 ;Mintz, 1962 Tarkowski,1968 ;Ford et al,1974 ;McLaren, 1975). In an XX *-+ XY chimaera in which the strain combination allowed the identification of the source of the sperm using morphological criteria, no sperm from the XX cell line were detected (Burgoyne, 1976 …”
mentioning
confidence: 94%
“…Recent biochemical observations have confirmed that both Xs are functional in oocytes (Epstein, 1969 ;Gartler et al, 1972 ;Gartler, Liskay and Gant, 1973 ;Kozak, McLean and Eicher, 1974 ;Gartler, Andina and Gant, 1975 ; Mangia, Abbo-Halbach and Epstein, 1975) and probably also in oogonia (Migeon and Jelalian, 1977 (Goldstein and Wilson, 1974). These XY women have streak ovaries just like XO women, and it can again be argued that this is a consequence of X-dosage deficiency in the oocytes (Burgoyne, 1978 (Tarkowski, 1961 ;Mintz, 1962 Tarkowski,1968 ;Ford et al,1974 ;McLaren, 1975). In an XX *-+ XY chimaera in which the strain combination allowed the identification of the source of the sperm using morphological criteria, no sperm from the XX cell line were detected (Burgoyne, 1976 There is a considerable body of evidence supporting the generality of this conclusion.…”
mentioning
confidence: 99%